2013
DOI: 10.1111/ajes.12020
|View full text |Cite
|
Sign up to set email alerts
|

New and Current Evidence on Determinants of Aggregate Federal Personal Income Tax Evasion in the United States

Abstract: ABSTRACT. Using the most current data available, this study seeks to identify any new as well as traditional determinants of personal income tax evasion. A variety of empirical estimates find that income tax rates, the IRS audit rate and IRS penalty interest rates, and the unemployment rate all influence tax evasion. In addition, rarely investigated variables including the tax-free interest rate, the public's job approval rating of the president, and the public's dissatisfaction with government, along with pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Repaying evaded tax plus tax fine will decrease total expected utility, and hence discourage tax evasion. Although theoretically giving positive impact, many empirical researches have demonstrated that the impact of audit on tax compliance is not as strong as expected and tends to be inconsistent (Kirchler et al, 2008 (Cebula, 2013) or special rate (Kim, 2008).…”
Section: Tax Evasion Deterrence Approach and Hypothesesmentioning
confidence: 94%
“…Repaying evaded tax plus tax fine will decrease total expected utility, and hence discourage tax evasion. Although theoretically giving positive impact, many empirical researches have demonstrated that the impact of audit on tax compliance is not as strong as expected and tends to be inconsistent (Kirchler et al, 2008 (Cebula, 2013) or special rate (Kim, 2008).…”
Section: Tax Evasion Deterrence Approach and Hypothesesmentioning
confidence: 94%
“…Our study moves beyond the attempts to experimentally manipulate morale to quantify the impact of naturally occurring quasi-experimental variation in attitudes toward government on evasion, as measured by IRS administrative data. From this perspective, the most closely related predecessor is Cebula (2013), showing that the IRS time series on aggregate evasion is predicted by the public's dissatisfaction with government. Using more plausibly exogenous variation in attitudes, we confirm a causal link.…”
Section: Literature On Tax Moralementioning
confidence: 98%
“…Tax rate denotes the quantum of tax that a taxpayer pays in accordance with the taxable items and tax laws. Several studies in both developed and across developing countries have been undertaken in the domain of tax noncompliance and tax rate, and the findings show there is positive relationship (Guldana, 2013;Freire-Seré n & Panadé s, 2013;Cebula, 2013;Abiola & Asiweh, 2012;Mughal & Akram, 2012;Muhrtala & Ogundeji, 2013;Gurama, 2015;Ayuba et al, 2016;Sinnasamy & Bidin, 2017). Overall, these studies have shown that the tax rate is directly related to the taxpayers' ability to behave positively or negatively based on their opinion of tax noncompliance.…”
Section: Tax Ratementioning
confidence: 99%